2000
DOI: 10.3354/meps198157
|View full text |Cite
|
Sign up to set email alerts
|

Population ecology of the barnacle Chthamalus stellatus in the northwest Mediterranean

Abstract: This study examined patterns in the distnbution and demography of the barnacle Chthamalus steiiatus (Poli) at different spatial scales in the northwest Mediterranem. Prelirninary data indicated that the abundance and size of barnacles decreased from high-shore to low-shore habitats. The generality of these patterns was investigated at several locations (10s to 100s of km apart), at several sites within locations (100s to 1000s of m apart) and at different times. Patterns were consistent with the prelirninary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 26 publications
0
34
0
1
Order By: Relevance
“…Regional patterns were largely due to the low abundance of cyanobacteria and barnacles at Punta Bianca, the northernmost shore in the study, which also supported more mussels than the other shores. In a previous study, Benedetti-Cecchi et al (2000b) found considerably more variation in patterns of growth of barnacles among shores 10s to 100s of km apart than among quadrats 10s of cm apart. There was also considerable variability in recruitment of barnacles at the regional scale, although recruitment was much more variable among quadrats.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Regional patterns were largely due to the low abundance of cyanobacteria and barnacles at Punta Bianca, the northernmost shore in the study, which also supported more mussels than the other shores. In a previous study, Benedetti-Cecchi et al (2000b) found considerably more variation in patterns of growth of barnacles among shores 10s to 100s of km apart than among quadrats 10s of cm apart. There was also considerable variability in recruitment of barnacles at the regional scale, although recruitment was much more variable among quadrats.…”
Section: Discussionmentioning
confidence: 76%
“…Variation among tidal heights was significantly larger than horizontal variability at the scale of the patch for these organisms. Previous studies have shown that pre-emption of the substratum and postrecruitment mortality due to unknown processes can account for the decline in cover of barnacles from the top to the bottom of the shore , 2000b. Variation in recruitment might also contribute to these differences, as observed elsewhere (Grosberg 1982).…”
Section: Discussionmentioning
confidence: 92%
“…This result was in agreement with theoretical modelling and empirical laboratory studies indicating that when fluctuations in environmental forcing variables are strongly autocorrelated in time or space, long-lasting negative conditions for species persistence become more likely and this can increase the risk of extinction of organisms (Heino 1998, Pike et al 2004). Alternatively, the large fluctuations in abundance of Chthamalus stellatus observed under reduced variability of aerial exposure might be determined by chance effects, like the coincidence of aerial exposure with the timing of recruitment of barnacles (between May and August on our shores, Benedetti-Cecchi et al 2000). In this scenario, effects of the sequence of events rather than temporal variability per se would have driven temporal variance in the abundance of barnacles.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few papers quantified the relative contribution of newly settled, juvenile, or adult organisms to the distributional patterns of the same species, also distinguishing brooders from free-spawners (Åberg & Pavia 1997, Hyder et al 1998, Hughes et al 1999, Benedetti-Cecchi et al 2000, Jenkins et al 2000. There are 3 papers (Fowler-Walker & Connell 2002, Irving et al 2004, Kelaher et al 2004) that have examined spatial patterns over very broad spatial scales (1000s of kilometers), at the expense of detailed middle and/or small-scale analyses.…”
Section: Review Of the Literaturementioning
confidence: 99%